Human Resources Development Program in Islamic Commercial Banks - Mardhiyaturrositaningsih Mardhiyaturrositaningsih (Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Purpose - This study aims to explore competency development programs to improve sustainable finance in Islamic Commercial Banks.Method - This research is using qualitative research methods to explore human resource management in Islamic Commercial Banks. This research is an exploratory study of the human resource development program at Islamic Commercial Banks during the Covid-19 pandemic. The research identifies the structure, training and development costs and human resource development strategies.Result - The results of this research indicate that each bank has a diverse strategy in developing employee competency through training and development programs. The employee structure of Sharia Commercial Banks also varies according to organizational needs. However, in the educational aspect there are similarities in that the majority are dominated by undergraduate education levels. The allocation of training and development funds at several banks has decreased due to the Covid-19 pandemic. Implication - This study implies the important role of human resources in an organization and the need for strategies to increase employee competency.Originality- This paper provides information regarding the employee structure of Islamic Commercial Banks and the policies developed at each Islamic Commercial Bank in Indonesia.